Poorer attainment of hemoglobin A1C, blood pressure and LDL-cholesterol goals among younger adults with type 2 diabetes - Kim, Kim; Noran Naqiah Hairi; Feisul Idzwan Mustapha; Khalijah Mohd Yusof; Zainudin Mohd Ali; Foong, Ming Moy (Penerbit Universiti Kebangsaan Malaysia, 2021)
Concurrent attainment of glycated haemoglobin A1C, blood pressure, and LDL-cholesterol goals, or collectively known as the ‘ABC’ goals, help prevent cardiovascular complications in patients with type 2 diabetes (T2D). We aimed to determine the proportion of T2D patients who achieved all three ABC goals in Malaysia’s public health clinics. We also determined the association between age groups with the attainment of all the ABC goals. A cross-sectional analysis of the baseline findings from a retrospective open cohort study between 2013 and 2017 in Negeri Sembilan, Malaysia was conducted. The data was extracted from the National Diabetes Registry. The primary outcome was the proportion of patients who attained all three ABC goals. The exposure of interest was patients’ age groups, namely 18-44, 45-59 and ≥ 60 years. Multivariate logistic regression analysis was used to adjust demographics factors, comorbidities, complications and treatment profiles. Among 17,592 patients, the mean age was 59.1 years, with 56.3% females and 64.9% Malays. Overall, 4.5% (95% CI: 4.2-4.8) of the patients attained all the ABC goals. Compared to older adults aged ≥ 60 years, patients aged 18-44 and 45-59 years had adjusted odds ratios of 0.50 and 0.72, respectively, to achieve all the ABC goals. Ethnicity, body mass index, diabetes treatment modality, lipid-lowering agent and polypharmacy were independent factors associated with the outcome. In summary, achieving all the ABC goals in T2D patients is challenging, especially among younger adults. Our findings suggest that more targeted interventions should be directed towards this high-risk subpopulation.